(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article examines new approaches to improving the quality of vocational education in medical colleges, including the competency-based model, simulation-based training, the dual education system, the use of modern pedagogical technologies, and the enhancement of teachers’ professional skills. The study substantiates effective methods for developing practical skills among students of medical colleges.